The Effect of Combination of Polyvinyl alcohol and Alfa-cellulose on Physical and Chemical Properties Salam Leaves Ethanolic Extract Patch (Syzygium polyanthum (wight) walp.) - Dian Eka Ermawati; Novi Andriani (Majalah Farmaseutik, 2022)
Salam leaves contain the flavonoid as an anti-inflammatory at a dose of 2.1% w/w. Topical anti-inflammatory was chosen because it is easier to apply. A patch can release the active substance continuously for a long time, compared to gels and creams. Polymers are the main component of patch to control the speed of drug release. Polyvinyl alcohol and alpha-cellulose are polymers that can increase the rate of drug diffusion and form a strong film layer. This study aims to determine the effect of the combination of PVA and Alpha-cellulose on the physicochemical properties of the salam leaves ethanolic extract patch. This research was carried out by maceration of salam leaves using ethanol 96% then dispersed in a patch that was made with variations ratio of PVA and alpha-cellulose, namely 1:1; 3:1; 1:3. The patches were tested for physicochemical properties including organoleptic, pH, thickness, weight, folding endurance, and humidity. Statistical analysis of the test data used One Way ANOVA and Paired Samples T-Test with a confidence level of 95%. The results showed that the combination of PVA and alpha-cellulose polymer in the patch preparation had a significant effect on the weight, thickness, and moisture test, but did not affect an organoleptic, folding endurance, and pH test. Based on the parameters of the physicochemical properties test, the chosen formula was a patch with a ratio of PVA and alpha-cellulose 7:3 because it met the requirements for the patch preparation including the weight of 1.96-2.06 grams, thickness 1.15-1.18 mm, folding endurance >300 times, humidity 25.75 – 30.17% and pH 6.3 – 7.1. The selected formula contains flavonoids based on qualitative analysis using the TLC method.